2010
DOI: 10.1510/icvts.2009.221804
|View full text |Cite
|
Sign up to set email alerts
|

Importance of preoperative assessment of pulmonary venous anomaly for safe video-assisted lobectomy

Abstract: During the treatment of 86 patients with video-assisted thoracoscopic surgery (VATS) anatomical resection (include segmentectomy) within the last two years, we have encountered five patients (5.8%) with anomalous venous returns. Anomalous returns included: 1) common trunk of the left pulmonary vein; 2) right middle pulmonary vein (V4) draining into the inferior pulmonary vein (IPV); 3) left lingular vein (V4+5) draining into the IPV; 4) right posterior pulmonary vein (V2) draining directly into the left atrium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 9 publications
0
23
1
Order By: Relevance
“…The clinical implication of these anatomical variations regards pulmonary resections especially under videothoracoscopy in which the operator may be confronted to non-negligible disadvantages: reduction of the operating field or difficult vascular exposure, less understanding of the hilum anatomy, and lack of understanding of the path of the pulmonary veins, compared to open surgery. Knowing these anatomical variations and a precise examination of the preoperative CT scan is useful for all thoracic surgeons in order to perform a safe and precise surgical procedure [1,18]. Indeed, this preoperative assessment allowed us to avoid a venous wound or a post-operative lung infarction in our study.…”
Section: Discussionmentioning
confidence: 90%
“…The clinical implication of these anatomical variations regards pulmonary resections especially under videothoracoscopy in which the operator may be confronted to non-negligible disadvantages: reduction of the operating field or difficult vascular exposure, less understanding of the hilum anatomy, and lack of understanding of the path of the pulmonary veins, compared to open surgery. Knowing these anatomical variations and a precise examination of the preoperative CT scan is useful for all thoracic surgeons in order to perform a safe and precise surgical procedure [1,18]. Indeed, this preoperative assessment allowed us to avoid a venous wound or a post-operative lung infarction in our study.…”
Section: Discussionmentioning
confidence: 90%
“…Also, Wannasopa et al found that, in a study population of 300 patients, 3.3 % had right common trunk and left single venous ostium in 59 % [4]. Furthermore, Yamada et al, in 86 patients undergoing VATS operation, found, preoperatively, one patient with one left pulmonary ostium [5]. All these lead to the conclusion that the prevalence of common trunk is more often for the left drainage pulmonary pattern than the right one, and so, the surgeons should be more aware and careful during left lobectomy.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Interesting case reports and reviews concerning anomalies in pulmonary venous drainage have been moreover published in the current thoracic surgery literature in order to make major lung resections performed via less invasive approaches a safer procedure. 4,5 Here, we report the coexistence of multiple and rare pulmonary veins variants identified in an adult patient: each of them, if not recognized, could lead to intraoperative or early postoperative complications.…”
Section: Introductionmentioning
confidence: 92%
“…This important clinical issue in recent decades has also enabled anatomists, through dissection of human fixed cadaveric lungs, to identify variants in the number and course of pulmonary veins with particular care such as the medial and the lateral middle lobe pulmonary veins that drain, either as a common trunk or independently, directly into the left atrium or into the inferior pulmonary vein . Interesting case reports and reviews concerning anomalies in pulmonary venous drainage have been moreover published in the current thoracic surgery literature in order to make major lung resections performed via less invasive approaches a safer procedure . Here, we report the coexistence of multiple and rare pulmonary veins variants identified in an adult patient: each of them, if not recognized, could lead to intraoperative or early postoperative complications.…”
Section: Introductionmentioning
confidence: 94%